Electron Localization in Molecular Fragmentation of H2 by Carrier-Envelope Phase Stabilized Laser Pulses - Kremer, Manuel; Fischer, Bettina; Feuerstein, Bernold; de Jesus, Vitor L. B.; Sharma, Vandana; Hofrichter, Christian; Rudenko, Artem; Thumm, Uwe; Schröter, Claus Dieter; Moshammer, Robert; Ullrich, Joachim (My University, 2009)
Fully differential data for H2 dissociation in ultrashort (6 fs, 760 nm), linearly polarized, intense (0.44 PW/cm2) laser pulses with a stabilized carrier-envelope phase (CEP) were recorded with a reaction microscope. Depending on the CEP, the molecular orientation, and the kinetic energy release (KER), we find asymmetric proton emission at low KERs (0–3 eV), basically predicted by Roudnev and Esry, and much stronger than reported by Kling et al. Wave packet propagation calculations reproduce the salient features and discard, together with the observed KER-independent electron asymmetry, the first ionization step to be the reason for the asymmetric proton emission.